2020
DOI: 10.1021/acs.est.0c00234
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Novel Per- and Polyfluoroalkyl Substances in Mice Dosed with an Aqueous Film-Forming Foam

Abstract: Per-and polyfluoroalkyl substances (PFASs) are widespread in the blood of the general human population, and their bioaccumulation is of considerable scientific and regulatory interest. PFAS exposure resulting from aqueous film-forming foam (AFFF) ingestion is poorly understood due to the complexity of AFFF mixtures and the presence of polyfluorinated substances that may undergo metabolic transformation. C57BL/6 mice were dosed with an AFFF primarily containing electrochemically fluorinated PFASs for 10 days, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 51 publications
(113 reference statements)
5
43
0
Order By: Relevance
“…Most PFAS identified in this study were also reported by Houtz et al (2013) [ 49 ], Barzen-Hanson et al (2017) [ 2 ], and McDonough et al (2020) [ 29 ] for the same or similar AFFF commercial products. We qualified C 4 and C 6 perfluoroalkyl sulfonamide amino carboxylates and perfluoroalkyl sulfonamido amines that were reported by Houtz et al One pentafluorosulfide-containing eight perfluorocarbon PFAS (8-F5S-PFOS) found in AFFF was also reported by Barzen-Hanson et al We qualified four of six PFOS-substituted compounds (H-PFOS, U-PFOS, Cl-PFOS, and K-PFOS) and one of two PFDS-substituted compounds (H-PFDS) reported by McDonough et al A C 6 containing phosphonic acid and ester functional groups (8:2 monoPAP-diEes) identified in this study was detected in PFAS-contaminated soil (from paper sludge) in Germany [ 50 ].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Most PFAS identified in this study were also reported by Houtz et al (2013) [ 49 ], Barzen-Hanson et al (2017) [ 2 ], and McDonough et al (2020) [ 29 ] for the same or similar AFFF commercial products. We qualified C 4 and C 6 perfluoroalkyl sulfonamide amino carboxylates and perfluoroalkyl sulfonamido amines that were reported by Houtz et al One pentafluorosulfide-containing eight perfluorocarbon PFAS (8-F5S-PFOS) found in AFFF was also reported by Barzen-Hanson et al We qualified four of six PFOS-substituted compounds (H-PFOS, U-PFOS, Cl-PFOS, and K-PFOS) and one of two PFDS-substituted compounds (H-PFDS) reported by McDonough et al A C 6 containing phosphonic acid and ester functional groups (8:2 monoPAP-diEes) identified in this study was detected in PFAS-contaminated soil (from paper sludge) in Germany [ 50 ].…”
Section: Discussionsupporting
confidence: 85%
“…We calculated pseudo-bioconcentration factors (BCF pseudos ) for noncovalently bound and potentially covalently bound fractions separately to evaluate patterns related to perfluorocarbon chain length and functional groups ( Figure 5 ). BCF pseudo serves as a quantitative benchmarking technique to cross-compare bioaccumulation potentials of novel PFAS using qualitative screening data [ 29 ]. The BCF pseudo was calculated for each PFAS as follows: where A i ,sample is the peak area of compound i detected in the protein aliquot or pellet; A L-PFOS,sample is the peak area of L-PFOS detected in the protein aliquot or pellet; A L-PFOS,AFFF is the peak area of L-PFOS detected in neat AFFF dilutions; and A i ,AFFF is the peak area of compound i detected in neat AFFF dilutions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure to the perfluorooctanesulfonamido ammonium (PFOSAmS), for example, resulted in the detection of 74 biotransformation products (Han et al 2021). This number is in line with the 92 parent and biotransformation products detected in mice exposed to PFAS-containing aqueous film-forming foam (AFFF) (McDonough et al 2020). Accordingly, human PFAS risk assessment strategies likely need to consider internal PFAS mixtures from direct accumulation and, as an additional source, biotransformation.…”
Section: Pfas Biotransformationmentioning
confidence: 73%